La politique québécoise Les enfants au cœur de nos choix : Un pari audacieux néanmoins gagnant - Renée B. Dandurand (Enfances, Familles, Générations, 2020)
Research Framework: After establishing an initial family policy (with pro-birth undertones) in 1988, Quebec changed direction in 1997 by enacting new child-focused measures, i.e. Les enfants au cœur de nos choix. By offering family allowances, low-cost school child care services and the promise of a better parental insurance plan, the new policy pursued three objectives: promoting early childhood development and equal opportunities, facilitating a work-family balance and ensuring increased aid to low-income families. In 1997 the policy surprised many, given the substantial budget deficit of the time. The government was shifting from a policy based on population growth to a generous socio-democratic strategy. Objectives: After presenting the historical context that gave rise to the implementation of an explicit family policy in Quebec, this article explains the demographic, political and economic circumstances in play prior to the adoption of the new child-focused policy. Methodology: The analysis of the Quebec family policy presented in this article is largely based on the author's observations and her analysis of this policy in her career. Results: The analysis reveals that change in family policy to be a bold gamble, one that has no equivalent in North America. Conclusions: Close examination of various studies analyzing the impacts of the policy suggests that the gamble can be considered to have been a success, one that has led to significant advances for women. Contribution: This article provides a socio-historical reflection on the Quebec family policy and explains the context - demographic, political and economic – in which it was made and during the 1990s, its transition from a natalist policy to a socio-democratic policy that collectivizes reproductive work with young children. In addition, it provides an interpretation of the meaning and scope of this policy.